Effect of Different Administered Doses of Capsaicin and Titanium Implant Osseointegration - Bingul, Muhammet Bahattin; Gul, Mehmet; Dundar, Serkan; Sokmen, Kevser; Artas, Goekhan; Polat, Mehmet Emrah; Ozcan, Erhan Cahit (Mdpi, 2024)
Background and Objectives: This study aimed to evaluate the histological and biochemical effects of capsaicin on implant osseointegration and oxidative stress. Materials and Methods: Male Wistar albino rats weighing between 250 and 300 g were used in this study. Twenty-four rats were randomly divided into three equal groups: implant + control (n = 8), implant + capsaicin-1 (n = 8), and implant + capsaicin-2 (n = 8). Additionally, 2.5 mm diameter and 4 mm length titanium implants were surgically integrated into the corticocancellous bone parts of the femurs. In the treatment groups, rats were injected intraperitoneally with 25 mg/kg (implant + capsaicin-1) and 50 mg/kg (implant + capsaicin-2) of capsaicin. No additional applications were made in the control group. Three rats in total died during and after the experiment as a result of the analyses performed on 21 animals. Results: The highest total antioxidant status value was found in capsaicin dose 2, according to the analysis. The control group had the highest total oxidant status and oxidative stress index values, while group 2 of capsaicin had the lowest. After analysis, we found that there was no observed positive effect on osteointegration in this study (p > 0.05), although the bone implant connection was higher in the groups treated with capsaicin. Conclusions: A positive effect on osteointegration was not observed in this study. This may be due to osteoclast activation. However, it was found that it has a positive effect on oxidative stress. Osteoclast activation may be the cause of this phenomenon. Capsaicin was found to have a positive effect on oxidative stress (p < 0.05). It was also observed to have a positive effect on oxidative stress.
Keywords: capsaicin; oxidative stress; osseointegration; bone implant connection